Extracellular Sortilin Proteopathy Relative to β-Amyloid and Tau in Aged and Alzheimer’s Disease Human Brains - Tu, Tian; Jiang, Juan; Zhang, Qi-Lei; Wan, Lily; Li, Ya-Nan; Pan, Aihua; Manavis, Jim; Yan, Xiao-Xin (Frontiers in Aging Neuroscience, 2020)
Amyloid plaques and neurofibrillary tangles (NFT) are hallmark lesions of Alzheimer’s disease (AD) related to β-amyloid (Aβ) deposition and intraneuronal phosphorylated-tau (pTau) accumulation. Sortilin C-terminal fragments (shortened as “sorfra”) can deposit as senile plaque-like lesions within AD brains. The course and pattern of sorfra plaque formation relative to Aβ and pTau pathogenesis remains unknown. In the present study cerebral and subcortical brain regions in postmortem human brains (n=46) from aged and AD subjects were stained using multiple markers (6E10, β-secretase 1, pTau and sortilin antibodies, as well as Bielschowsky silver stain). The course and pattern of sorfra plaque formation relative to Thal Aβ and Braak NFT pathogenic stages were determined. Sorfra plaques occurred in the temporal, inferior frontal and occipital neocortices in cases with Thal 1 and Braak III stages. They were also found additionally in the hippocampal formation, amygdala and associative neocortex in cases with Thal 2-4 and Braak IV-V. Lastly, they were also found in the primary motor, somatosensory and visual cortices in cases with Thal 4-5 and Braak VI. Unlike Aβ and pTau pathologies, sorfra plaques did not occur in subcortical structures in cases with Aβ/pTau lesions in Thal 3-5/Braak IV-VI stages. We establish here that sorfra plaques are essentially a cerebral proteopathy. We believe that the development of sorfra plaques in both cortical and hippocampal regions proceeds in a typical spatiotemporal pattern, and the stages of cerebral sorfra plaque formation partially overlap with that of Aβ and pTau pathologies.